(untitled) (Journal of Nobel Medical College, 2021)
Background: Lichen planus is an immune mediated disease that affects the skin and the mucous membranes. Although the etiology and pathogenesis are not fully understood, it is believed that lichen planus represents a T-cell-mediated inflammatory disorder which produces disturbances of lipid metabolism. Materials and Methods: Patients with the clinical diagnosis of lichen planus were included in the study after taking informed written consent. In total 40 patients were included in the study. Serum lipid profile was performed in the medical laboratory of Nobel Medical College Teaching Hospital. Results: Out of 40 patients, 13(32.5%) patients had dyslipidemia. Overall dyslipidemia was seen more in female patients (53.8%) than in male patients (46.2%). In our study, hypertrophic (32.5%) followed by eruptive (27%) and mucosal (25%) lichen planus were the most common variant. Conclusion: This study demonstrated that about one-third of lichen planus patients showed deranged lipid levels in blood so for patients presenting with lichen planus physicians should consider screening them for dyslipidemia.